Pengaruh Karakteristik Wirausaha, Kreativitas, dan Pengalaman Terhadap Keberhasilan Usaha Olahan Kedelai di Kecamatan Ambulu - Nanda Khoirun Nisa; Hermawan, Haris; Izzuddin, Ahmad (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the effect of entrepreneurial characteristics, creativity, and business experience on the success of soybean processing businesses in Ambulu District, both partially and simultaneously. The research method used is a quantitative method with a survey approach. The population of this study is all soybean processing business actors in Ambulu District, with a sample of 60 respondents selected using the total sampling technique. Data were collected through questionnaires using a Likert scale and then analyzed using multiple linear regression tests, t-tests, F-tests, and the coefficient of determination test. The results of the study show that partially, the entrepreneurial characteristics variable does not have a significant effect on business success, while the creativity and business experience variables have a positive and significant effect. Simultaneously, the three variables (entrepreneurial characteristics, creativity, and business experience) significantly affect the success of soybean processing businesses. These findings imply that business actors need to further develop creativity and enrich practical experience as the main factors to improve their business success, while strengthening entrepreneurial characteristics remains important as the foundation of business sustainability. This study is expected to contribute to MSME actors, local governments, and educational institutions in designing coaching programs that focus on strengthening creativity and experience, while still paying attention to the development of adaptive and innovative entrepreneurial characteristics.